Efektivitas Penanganan Produk Yang Beredar Oleh BPOM Surabaya: Dampak Bagi Konsumen dan Kesehatan Masyarakat - Mariana Mugiono; Steven, Anthony; Athina Indradewi, Astrid; Carissa Amanda Siswanto (LPPM Universitas Ekasakti Padang, 2024)
Researches asses problems related to the role of BPOM in providing service to ensure all products that have and haven't been released to public are safe to consume. BPOM have those products gone through several phases again and again, both before release (pre-market) and after release (post-arket), to ensure that those products are safe to consume. BPOM must also work together with state officials and people in general to speed up the process of detecting illegal products. If such products, which has dangerous effects on consumer's health, are found, BPOM must immediately take a decisive action by removing release permit, withdrawing, reassess, destroying the products, and invoking the penal law if needed. To provide maximum protection for consumers, BPOM must always be on alert to oversee products that have and haven't been released in ensuring that they are safe to consume. In conclusion, BPOM must always give an information update for any products that have been released to public